A method for preparing high-performance copper-tin-10 alloy powder
Copper-tin 13 alloy powder is prepared by smelting and mixing method and undergoing multiple steps of treatment. Combined with the secondary mixing and the addition of phosphorus copper powder and lubricant, the problems of unsatisfactory compression, green strength and sintering shrinkage in the prior art are solved, and the preparation of high-performance copper-tin 10 alloy powder is realized.
Patent Information
- Application Number
- CN202410637621.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-05-22
AI Technical Summary
In the prior art, copper tin 10 alloy powder is prepared by diffusion of copper powder and prealloy powder, and its compressibility is limited, and the green body strength and sintering shrinkage rate are not ideal.
Copper-tin 13 alloy powder was prepared by smelting and mixing method, and was treated by high-pressure water atomization, high-speed centrifugation dehydration and drying. Then, the primary mixing and diffusion reduction treatment were carried out, and the final crushing and screening and secondary mixing treatment were carried out, and phosphorus copper powder and lubricant were added to improve the performance of the finished copper-tin 10 alloy powder.
Effectively reduce the composition segregation in the alloy, improve the compression density, green body strength and crush strength, improve the sintering shrinkage rate, and significantly improve the overall mechanical properties of copper-tin 10 alloy powder.
Smart Images

Figure CN118616721B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of alloy powder production, in particular to a method for preparing high-performance copper-tin-10 alloy powder. Background Art
[0002] Copper-tin alloy powder is mainly used in oil-containing bearings, diamond tools and other industries. Among them, CuSn10 powder is used as the basic raw material for oil-containing bearings due to its better pressing and sintering performance. There are several methods for preparing CuSn10 powder. One is to mechanically mix copper powder and tin powder in a ratio of 90:10, the second is to partially alloy copper powder and tin powder by diffusion alloying, and the third method is to prepare copper-tin powder by pre-alloyed water atomization. Although the above methods have solved the problem of high bulk ratio of powder to varying degrees, there is still a large gap in porosity, which is specifically reflected in the uneven powder composition, the difficult to control sintering size change rate, and the poor green strength. To solve the above problems, in the public technology, the invention patent CN111331129A is a method for preparing low loose density CuSn10 powder, which is mixed with copper powder, copper-tin 10 pre-alloyed powder produced by a pre-alloying method and additives. The ratio of copper powder to pre-alloyed powder is 1:2. Since pure copper powder is added to the pre-alloyed powder, the physical properties of the original pure copper powder and tin powder mixture are changed. This is a product prepared by diffusion of copper powder and pre-alloyed powder, attempting to use diffusion to avoid the disadvantage of relatively high component segregation of copper-tin 10 alloy powder. Although the overall performance is improved compared to single pre-alloy or mixed powder, its compressibility is limited, and the green strength and sintering shrinkage are also not ideal. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing high-performance copper-tin-10 alloy powder, so as to solve the problem that the copper-tin-10 alloy powder is prepared by diffusion of copper powder and pre-alloyed powder in the prior art, but the copper-tin-10 alloy powder prepared by diffusion of copper powder and pre-alloyed powder alone has limited improvement in compressibility, and the green strength and sintering shrinkage are not ideal.
[0004] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing high-performance copper-tin-10 alloy powder, comprising the following steps:
[0005] (1) Smelting and mixing: 87% electrolytic copper plate and 13% tin ingot are smelted together to obtain a copper-tin 13 alloy liquid with a tin content of 13%;
[0006] (2) high-pressure water atomization: the copper-tin-13 alloy liquid is prepared into copper-tin-13 alloy powder by high-pressure water atomization, and then subjected to high-speed centrifugal dehydration treatment using a scraper centrifuge;
[0007] (3) Drying treatment: placing the dehydrated copper-tin-13 alloy powder in a steel belt drying furnace for drying;
[0008] (4) Primary mixing: the dried copper-tin 13 alloy powder and the pure copper powder prepared from the electrolytic copper plate are pumped into a mixing tank in a predetermined ratio for mixing to generate a primary copper-tin mixed powder;
[0009] (5) Diffusion reduction: placing the copper-tin primary mixed powder in a reduction furnace, and performing diffusion reduction treatment under a high temperature, nitrogen and hydrogen reduction environment to obtain a copper-tin 11 aggregate with a tin content of 10.5-11.5%;
[0010] (6) Crushing and screening: crushing and screening the copper-tin-11 aggregates, controlling the crushing frequency to be 20 Hz-30 Hz, and screening the copper-tin-11 alloy powder to have a particle size of -80 mesh;
[0011] (7) Secondary mixing: the copper-tin-11 alloy powder with a particle size of -80 mesh is mixed with 10-13% of the pure copper powder, 0.1% of phosphor copper powder and 0.5% of lubricant in a predetermined proportion and stirred for about 40 minutes to obtain a finished copper-tin-10 alloy powder;
[0012] (8) Experimental packaging: The finished copper-tin-10 alloy powder is subjected to a sintering test, and the finished copper-tin-10 alloy powder that passes the test is packaged.
[0013] Furthermore, in the secondary mixture, the mixing ratio of the copper-tin-11 alloy powder and 10-13% of the pure copper powder is 10:1, wherein the particle size of the pure copper powder is -100 mesh.
[0014] Furthermore, the copper-tin-11 alloy powder is mixed with 10%, 12% or 13% of the pure copper powder, 0.1% of phosphor copper powder and 0.5% of lubricant.
[0015] Furthermore, in the primary mixing material, the composition ratio of the copper-tin-13 alloy powder to the pure copper powder is 10:3, wherein the bulk ratio of the copper-tin-13 alloy powder is 3.15-3.33 g / cm 3 The particle size is between -325 mesh ≥75%; the looseness ratio of the pure copper powder is ≤2.6g / cm 3 , Particle size -325 mesh ≥75%.
[0016] Furthermore, in the diffusion reduction, the reduction temperature of the copper-tin primary mixed powder is 540-600° C., and the reduction time is 160 min-180 min.
[0017] Furthermore, in the crushing and screening, a fine crusher and a screening machine are used to crush and screen the copper-tin-11 aggregates, the frequency of the fine crusher is set to 20 Hz, the crushing mesh is -80 mesh, wherein the bulk ratio of the copper-tin-11 alloy powder after screening is 2.45-2.55 g / cm 3Between, particle size -325 mesh ≤40%.
[0018] Furthermore, the smelting and mixing is carried out by high-temperature smelting, and the smelting temperature is 1100° C. to 1200° C., and the electrolytic copper and the tin ingot are smelted to form an alloy liquid phase.
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] 1. Compared with the copper-tin-10 alloy powder prepared by diffusing copper powder and pre-alloyed powder in the prior art, the present invention first prepares the copper-tin-13 alloy powder by smelting and mixing, and then performs high-pressure water atomization. Then, the copper-tin-13 alloy powder is subjected to high-speed centrifugal dehydration and drying treatment, followed by primary mixing and diffusion reduction treatment, and finally crushing, screening and secondary mixing treatment; the key lies in the secondary mixing treatment, in which the copper-tin-11 alloy powder that has completed diffusion reduction is crushed and re-screened, wherein the bulk ratio of the re-screened copper-tin-11 alloy powder is less than the bulk ratio of the copper-tin-13 alloy powder that has completed diffusion reduction. At this time, the re-screened copper-tin-11 alloy powder is mixed with pure copper powder in proportion, and 0.1% phosphor copper powder and 0.5% lubricant are added to mix to form a finished copper-tin-10 alloy powder. The copper-tin-11 alloy powder that has been crushed for the second time in the present invention is again mixed uniformly in advance to obtain the finished copper-tin-10 alloy powder, instead of relying on the later diffusion process to homogenize the composition, which can effectively reduce the component segregation in the alloy, while improving the pressing density, green strength and crushing strength, etc., and then, phosphor copper powder and lubricant are added. The phosphorus element in the phosphor copper powder can be used as a grain refiner to promote the formation of a finer and more uniform grain structure during the alloying process, which helps to improve the overall mechanical properties of the material and increase the sintering shrinkage rate; the lubricant can reduce the friction between the powder particles, making it easier to disperse and evenly disperse the powder during mixing, which helps to improve the uniformity and efficiency of the mixing. The copper-tin-10 alloy powder prepared through the above steps has higher performance.
[0021] 2. The copper-tin 11 alloy powder formed after heat treatment is finely crushed and screened to ensure the fineness and uniformity of the powder. In particular, through the secondary crushing and screening process, the bulk ratio of the screened copper-tin 11 alloy powder is 2.45-2.55g / cm 3 The particle size is -325 mesh ≤ 40%, which is significantly better than the loose ratio of the initial copper-tin 13 alloy powder, which provides a more compact and uniform powder base for subsequent mixing.
[0022] 3. The present invention firstly adopts an alloy smelting method, in which copper and tin are first smelted by high-temperature smelting to form an alloy liquid phase, and then a copper-tin 13 alloy powder is prepared by high-pressure water atomization, and then centrifugal dehydration and drying are performed. This method can improve the alloying degree of copper and tin and reduce the probability of component segregation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described below in conjunction with the accompanying drawings:
[0024] Figure 1 The green strength test graph of copper-tin-10 alloy powder obtained by the preparation method of the high-performance copper-tin-10 alloy powder of the present invention;
[0025] Figure 2 This is a SEM image of the copper-tin-10 alloy powder prepared in Example 2 of the present invention;
[0026] Figure 3 This is the SEM image of the CuSn10 powder prepared in Comparative Example 1. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0028] The technical solution of the present invention is described in detail with specific embodiments below. The following specific embodiments can be combined or replaced with each other according to actual conditions, and the same or similar concepts or processes may not be described in detail in some embodiments.
[0029] like Figure 1 to Figure 2 As shown, the present invention provides a method for preparing a high-performance copper-tin-10 alloy powder. The present invention includes three preferred embodiments. The process preparation steps of the copper-tin-10 alloy powder in the three embodiments are the same: the specific process steps include;
[0030] S1 smelting and mixing: smelting electrolytic copper plates with a composition ratio of 87% and tin ingots with a composition ratio of 13% to obtain a copper-tin 13 alloy liquid with a tin content of 13%;
[0031] S2 high-pressure water atomization: preparing the copper-tin-13 alloy liquid into copper-tin-13 alloy powder by high-pressure water atomization, and performing high-speed centrifugal dehydration treatment using a scraper centrifuge;
[0032] S3 drying treatment: placing the dehydrated copper-tin-13 alloy powder in a steel belt drying furnace for drying;
[0033] S4 primary mixing: pumping the dried copper-tin 13 alloy powder and the pure copper powder prepared from the electrolytic copper plate into a mixing tank in a predetermined ratio for mixing to generate a primary copper-tin mixed powder;
[0034] S5 diffusion reduction: placing the copper-tin primary mixed powder in a reduction furnace, and performing diffusion reduction treatment under a high temperature, nitrogen and hydrogen reduction environment to obtain a copper-tin 11 aggregate with a tin content of 10.5-11.5%;
[0035] S6 crushing and screening: crushing and screening the copper-tin-11 aggregates, controlling the crushing frequency to be 20 Hz-30 Hz, and screening the copper-tin-11 alloy powder to have a particle size of -80 mesh;
[0036] S7 secondary mixing: the copper-tin-11 alloy powder with a particle size of 80 mesh is mixed with 10-13% of the pure copper powder and 0.5% of the lubricant in a predetermined proportion and stirred for about 40 minutes to obtain a finished copper-tin-10 alloy powder; wherein the lubricant can be selected from zinc stearate, micro wax powder, carboxymethyl cellulose or sodium silicate. The present invention uses micro wax powder as the lubricant, and the micro wax powder is derived from natural or synthetic wax. The micro wax powder has excellent lubricity and film-forming properties. It can form a thin lubricating film on the surface of the powder particles, reduce direct contact between powders, thereby reducing friction and improving the uniformity of the mixture. The advantages of the micro wax powder are that it has good chemical stability, is environmentally friendly, and is easy to volatilize during high-temperature sintering, will not remain in the final product, and has little effect on the performance of the alloy.
[0037] S8 Experimental packaging: a sintering test is performed on the finished copper-tin-10 alloy powder, and the finished copper-tin-10 alloy powder that passes the test is packaged.
[0038] Embodiment 1:
[0039] S1: melting an electrolytic copper plate with a composition ratio of 87% and a tin ingot with a composition ratio of 13% at a high temperature of 1200° C. into an alloy liquid phase to obtain a copper-tin 13 alloy liquid with a tin content of 13%;
[0040] S2: The obtained copper-tin-13 alloy liquid is prepared into copper-tin-13 alloy powder by high-pressure water atomization at 85 MPa, and the copper-tin-13 alloy powder enters a scraper centrifuge with high-pressure atomized water to achieve high-speed centrifugal dehydration;
[0041] S3: placing the dehydrated copper-tin-13 alloy powder in a steel belt drying furnace for drying;
[0042] S4: Pumping the dried copper-tin 13 alloy powder and the pure copper powder prepared from the electrolytic copper plate into a mixing tank in a ratio of 10:3 to mix them to generate a copper-tin primary mixed powder; wherein the bulk ratio of the copper-tin 13 alloy powder obtained by the above steps S1-S3 is 3.15-3.33 g / cm 3 Between, particle size -325 mesh ≥75%, the loose ratio of pure copper powder selected is ≤2.6g / cm 3 , Particle size -325 mesh ≥75%.
[0043] S5: placing the copper-tin primary mixed powder in a reduction furnace for heat treatment for 160 minutes, introducing hydrogen and nitrogen into the reduction furnace and keeping the temperature in the reduction furnace stable at 540° C.-600° C., and performing diffusion reduction treatment on the copper-tin primary mixed powder under high temperature, hydrogen and nitrogen atmosphere to obtain a copper-tin 11 aggregate with a tin content of 9%;
[0044] S6 Crushing and Screening: The obtained copper-tin-11 aggregates are crushed and screened by a fine crusher and a screener. The frequency of the fine crusher is set to 20Hz. The crushed powder enters the screener and passes through an 80-mesh screen to obtain a copper-tin-11 alloy powder with a crushing mesh of -80. The copper-tin-11 alloy powder that does not pass through the screen enters the circulation channel again for secondary crushing and screening. The bulk ratio of the copper-tin-11 alloy powder after screening is 2.45-2.55g / cm 3 Between -325 mesh ≤ 40%; It can be seen intuitively that the bulk ratio of the copper-tin 11 alloy powder after crushing and screening (2.45-2.55g / cm 3 The particle size is -325 mesh ≤ 40%, which is significantly smaller than the bulk ratio of copper-tin 13 alloy powder produced by high-pressure water mist method, which is 3.15-3.33 g / cm 3 Between, particle size -325 mesh ≥75%.
[0045] S7 Secondary mixing: Mix the copper-tin-11 alloy powder with a particle size of -80 mesh and 10% of the pure copper powder at a ratio of 10:1, and add 0.1% phosphor copper powder and 0.5% micro wax powder to mix and stir for about 40 minutes at a stirring speed of 7-10r / min. / M i n , to obtain finished copper-tin 10 alloy powder;
[0046] S8 Experimental Packaging: A sintering test was performed on the finished copper-tin-10 alloy powder. The sintering test results showed that the finished copper-tin-10 alloy powder prepared in this embodiment had a compacting density of 6.2 g / cm 3 The green strength reached an average of 13MPa, the shrinkage rate was 1.55%, and the crushing strength was 265MPa. Finally, the finished copper-tin 10 alloy powder that passed the test was packaged.
[0047] The sintering test data of Example 1 are shown in Table 1 below. Table 1 is the sintering test data of the copper-tin-10 alloy powder prepared in Example 1 of the present invention:
[0048]
[0049] Table 1
[0050] Embodiment 2:
[0051] S1: melting an electrolytic copper plate with a composition ratio of 87% and a tin ingot with a composition ratio of 13% at a high temperature of 1200° C. into an alloy liquid phase to obtain a copper-tin 13 alloy liquid with a tin content of 13%;
[0052] S2: The obtained copper-tin-13 alloy liquid is prepared into copper-tin-13 alloy powder by high-pressure water atomization at 85 MPa, and the copper-tin-13 alloy powder enters a scraper centrifuge with high-pressure atomized water to achieve high-speed centrifugal dehydration;
[0053] S3: placing the dehydrated copper-tin-13 alloy powder in a steel belt drying furnace for drying;
[0054] S4: Pumping the dried copper-tin 13 alloy powder and the pure copper powder prepared from the electrolytic copper plate into a mixing tank in a ratio of 10:3 to mix them to generate a copper-tin primary mixed powder; wherein the bulk ratio of the copper-tin 13 alloy powder obtained by the above steps S1-S3 is 3.15-3.33 g / cm 3 Between, particle size -325 mesh ≥75%, the loose ratio of pure copper powder selected is ≤2.6g / cm 3 , Particle size -325 mesh ≥75%.
[0055] S5: placing the copper-tin primary mixed powder in a reduction furnace for heat treatment for 160 minutes, introducing hydrogen and nitrogen into the reduction furnace and keeping the temperature in the reduction furnace stable at 540° C.-600° C., and performing diffusion reduction treatment on the copper-tin primary mixed powder under high temperature, hydrogen and nitrogen atmosphere to obtain a copper-tin 11 aggregate with a tin content of 9%;
[0056] S6 Crushing and Screening: The obtained copper-tin-11 aggregates are crushed and screened by a fine crusher and a screener. The frequency of the fine crusher is set to 20Hz. The crushed powder enters the screener and passes through an 80-mesh screen to obtain a copper-tin-11 alloy powder with a crushing mesh of -80 mesh. The copper-tin-11 alloy powder that has not passed through the screen enters the circulation channel again for secondary crushing and screening. The bulk ratio of the copper-tin-11 alloy powder after screening is 2.45-2.55g / cm 3 The particle size is between -325 mesh and ≤40%. It can be seen that the bulk ratio of the copper-tin 11 alloy powder after crushing and screening is between 2.45 and 2.55 g / cm 3 The particle size is between -325 mesh ≤40%, which is significantly smaller than the bulk ratio of copper-tin 13 alloy powder produced by high-pressure water mist method, which is 3.15-3.33g / cm 3 Between, particle size -325 mesh ≥75%.
[0057] S7 Secondary mixing: Mix the copper-tin-11 alloy powder with a particle size of -80 mesh and 12% of the pure copper powder at a ratio of 10:1, and add 0.5% of micro wax powder to mix and stir for about 40 minutes at a stirring speed of 7-10r / min. / M i n , to obtain finished copper-tin 10 alloy powder;
[0058] S8 Experimental Packaging: A sintering test was performed on the finished copper-tin-10 alloy powder. The sintering test results showed that the finished copper-tin-10 alloy powder prepared in this embodiment had a compacting density of 6.2 g / cm 3 The green strength reached an average of 14MPa, the shrinkage rate was 1.57%, and the crushing strength was 268MPa. Finally, the finished copper-tin 10 alloy powder that passed the test was packaged.
[0059] The sintering test data of Example 2 are shown in Table 2 below. Table 2 is the sintering test data of the copper-tin-10 alloy powder prepared in Example 2 of the present invention:
[0060]
[0061] Table 2 Example 3:
[0062] S1: melting an electrolytic copper plate with a composition ratio of 87% and a tin ingot with a composition ratio of 13% at a high temperature of 1200° C. into an alloy liquid phase to obtain a copper-tin 13 alloy liquid with a tin content of 13%;
[0063] S2: The obtained copper-tin-13 alloy liquid is prepared into copper-tin-13 alloy powder by high-pressure water atomization at 85 MPa, and the copper-tin-13 alloy powder enters a scraper centrifuge with high-pressure atomized water to achieve high-speed centrifugal dehydration;
[0064] S3: placing the dehydrated copper-tin-13 alloy powder in a steel belt drying furnace for drying;
[0065] S4: Pumping the dried copper-tin 13 alloy powder and the pure copper powder prepared from the electrolytic copper plate into a mixing tank in a ratio of 10:3 to mix them to generate a copper-tin primary mixed powder; wherein the bulk ratio of the copper-tin 13 alloy powder obtained by the above steps S1-S3 is 3.15-3.33 g / cm 3 Between, particle size -325 mesh ≥75%, the loose ratio of pure copper powder selected is ≤2.6g / cm 3 , Particle size -325 mesh ≥75%.
[0066] S5: placing the copper-tin primary mixed powder in a reduction furnace for heat treatment for 160 minutes, introducing hydrogen and nitrogen into the reduction furnace and keeping the temperature in the reduction furnace stable at 540° C.-600° C., and performing diffusion reduction treatment on the copper-tin primary mixed powder under high temperature, hydrogen and nitrogen atmosphere to obtain a copper-tin 11 aggregate with a tin content of 11%;
[0067] S6 Crushing and Screening: The obtained copper-tin-11 aggregates are crushed and screened by a fine crusher and a screener. The frequency of the fine crusher is set to 20Hz. The crushed powder enters the screener and passes through an 80-mesh screen to obtain a copper-tin-11 alloy powder with a crushing mesh of -80 mesh. The copper-tin-11 alloy powder that has not passed through the screen enters the circulation channel again for secondary crushing and screening. The bulk ratio of the copper-tin-11 alloy powder after screening is 2.45-2.55g / cm 3 The particle size is between -325 mesh and ≤40%. It can be seen that the bulk ratio of the copper-tin 11 alloy powder after crushing and screening is between 2.45 and 2.55 g / cm 3 The particle size is between -325 mesh ≤40%, which is significantly smaller than the bulk ratio of copper-tin 13 alloy powder produced by high-pressure water mist method, which is 3.15-3.33g / cm 3 Between, particle size -325 mesh ≥75%.
[0068] S7 Secondary mixing: Mix the copper-tin-11 alloy powder with a particle size of -80 mesh and 13% of the pure copper powder at a ratio of 10:1, and add 0.1% phosphor copper powder and 0.5% micro wax powder, mix and stir for about 40 minutes at a stirring speed of 7-10r / Min to obtain a finished copper-tin-10 alloy powder;
[0069] S8 Experimental Packaging: A sintering test was performed on the finished copper-tin-10 alloy powder. The sintering test results showed that the finished copper-tin-10 alloy powder prepared in this embodiment had a compacting density of 6.2 g / cm 3 The average green strength reached 13MPa, the shrinkage rate was 1.53%, and the crushing strength was 267MPa; finally, the finished copper-tin 10 alloy powder that passed the test was packaged.
[0070] The sintering test data of Example 3 are shown in Table 3 below. Table 3 is the sintering test data of the copper-tin-10 alloy powder prepared in Example 3 of the present invention:
[0071]
[0072] Table 3
[0073] Comparative Example 1:
[0074] 1. A method for preparing CuSn10 powder with low bulk density, comprising the following contents:
[0075] (1) Pure copper powder prepared by water atomization method is selected, and the particle size of the water atomized pure copper powder is -200 mesh;
[0076] (2) copper-tin alloy powder prepared by water atomization method, with a particle size of -200 mesh and a tin content of >10-30%;
[0077] (3) selecting the above-mentioned pure copper powder and copper-tin alloy powder and mixing them in proportion, wherein the ratio of copper to copper-tin alloy powder is selected between >0-2.0 times according to the difference in tin content of the copper-tin alloy powder;
[0078] (4) The mixed powder is put into a reduction furnace for sintering: the reduction temperature is 400-700°C; (5) The sintered powder is crushed and sieved, and the particle size distribution is adjusted to obtain the finished powder.
[0079] Prepare CuSn10 powder according to the preparation method of low bulk density CuSn10 powder in Comparative Example 1, and record the sintering test data of the prepared CuSn10 powder;
[0080] As shown in Table 4 below, Table 4 is the sintering test data of the CuSn10 powder prepared in Comparative Example 1;
[0081]
[0082] Table 4
[0083]
[0084] Table 5
[0085] Table 5 is a data table comparing the average values of the sintering test data of Examples 1-3 selected in the present invention with the average values of the sintering test data of Comparative Example 1.
[0086] Result analysis:
[0087] From the comparison of the bulk ratios of the products prepared by S1-S6 in Tables 1-3 and those in Tables 4 and 5, it can be seen that the bulk ratios of the copper-tin-11 alloy powder prepared by the S1-S6 steps of the present invention (bulk ratio average 2.45-2.55 g / cm 3 The loose ratio is significantly lower than that in Table 4 of Comparative Example 1 (loose ratio average ≤ 3.7 g / cm 3 ), this is because the present invention adopts a smelting alloy method, firstly, copper and tin are smelted by high-temperature smelting to form an alloy liquid phase, and copper-tin-13 alloy powder is prepared by high-pressure water atomization, and centrifugal dehydration and drying are performed, and then the prepared copper-tin-13 alloy powder and pure copper powder are pumped into a mixing tank according to a predetermined ratio for mixing to obtain a copper-tin primary mixed powder, and the copper-tin primary mixed powder is subjected to diffusion reduction treatment in a high-temperature, nitrogen and hydrogen reducing environment, and the prepared copper-tin-11 aggregated blocks are crushed again to obtain copper-tin-11 alloy powder. This method can improve the alloying degree of copper and tin and reduce the probability of component segregation.
[0088] At the same time, it can be seen from Table 5 that the copper-tin-11 alloy powder obtained by the S1-S6 process steps is mixed with 10%, 12%, and 13% of pure copper powder in a ratio of 10:1 to obtain the finished copper-tin-10 alloy powder. The copper-tin-11 alloy powder is crushed and screened, and then subjected to secondary mixing. The copper-tin-10 alloy powder obtained by adding pure copper powder for mixing has a compacted density of 6.2 g / cm 3 When the green strength is much higher than that of the powder prepared by the direct diffusion method, the sintering shrinkage is also better than that of the powder prepared by the direct diffusion method, and the crushing strength is better. Compared with the production method of Comparative Example 1 in Table 5, the present invention combines the advantages of uniform pre-alloy components and good compressibility of pre-mixed powder, solves the problem of component segregation of the copper-tin 10 pre-mixed powder, and retains the excellent compressibility of the mixed powder.
[0089] again, Figure 2 This is the SEM image of the copper-tin-10 alloy powder prepared in Example 2. Figure 3 is the SEM diagram of comparative example 1, Figure 2 and Figure 3 As can be seen from Table 5, the average shrinkage of the finished copper-tin-10 alloy powder prepared in Example 2 is 1.53%, which is significantly higher than the average shrinkage of the CuSn10 powder prepared in Comparative Example 1, which is 1.03%.
[0090] Therefore, it is proved that the preparation method of the copper-tin-10 alloy powder disclosed in Examples 1-3 is superior to the prior art in that the copper-tin-10 alloy powder is crushed and screened before secondary mixing, and pure copper powder is added to reduce the uneven distribution (segregation) of the alloy elements. In particular, in the secondary mixing step, uniform mixing is performed to ensure that each powder particle has an appropriate distribution of components around it, thereby improving the uniformity of the overall alloy. Phosphorus copper powder is also added, and phosphorus and copper form a semi-metallic compound Cu3P as a crystal core grain refiner of the alloy, which promotes the formation of a finer and more uniform grain structure during the alloying process, which helps to improve the overall mechanical properties of the material and increase the sintering shrinkage rate. The copper-tin-10 obtained after mixing has a pressing density of 6.2 g / cm 3 The green strength of the powder is much higher than that of the powder prepared by the direct diffusion method, and the sintering shrinkage is also better than that of the powder prepared by the direct diffusion method, and it has better crushing strength; it solves the problem that the copper-tin 10 alloy powder prepared by the traditional direct diffusion method has low green strength and poor shrinkage at low density, while the CuSn10 powder prepared by the mixing method has the disadvantage of component segregation.
[0091] In addition to the above-mentioned preferred embodiments, the present invention also has other implementation modes. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work are within the scope of protection requested by the present invention.
Claims
1. A method for preparing high-performance copper-tin-10 alloy powder, characterized in that: The following steps are involved: (1) Smelting and mixing: 87% electrolytic copper plate and 13% tin ingot are smelted together to obtain a copper-tin 13 alloy liquid with a tin content of 13%; (2) high-pressure water atomization: the copper-tin-13 alloy liquid is prepared into copper-tin-13 alloy powder by high-pressure water atomization, and then subjected to high-speed centrifugal dehydration treatment using a scraper centrifuge; (3) Drying treatment: placing the dehydrated copper-tin-13 alloy powder in a steel belt drying furnace for drying; (4) Primary mixing: the dried copper-tin 13 alloy powder and the pure copper powder prepared from the electrolytic copper plate are pumped into a mixing tank in a predetermined ratio for mixing to generate a primary copper-tin mixed powder; (5) Diffusion reduction: placing the copper-tin primary mixed powder in a reduction furnace, and performing diffusion reduction treatment under a high temperature, nitrogen and hydrogen reduction environment to obtain a copper-tin 11 aggregate with a tin content of 10.5-11.5%; (6) Crushing and screening: crushing and screening the copper-tin-11 aggregates, controlling the crushing frequency to be 20 Hz-30 Hz, and screening the copper-tin-11 alloy powder to have a particle size of -80 mesh; (7) Secondary mixing: the copper-tin-11 alloy powder having a particle size of -80 mesh is mixed with 10-13% of the pure copper powder, 0.1% of phosphor copper powder and 0.5% of lubricant in a predetermined proportion and stirred for about 40 minutes to obtain a finished copper-tin-10 alloy powder; (8) Experimental packaging: performing a sintering test on the finished copper-tin-10 alloy powder, and packaging the finished copper-tin-10 alloy powder that passes the test; in; In the secondary mixing, the mixing ratio of the copper-tin-11 alloy powder and 10-13% of the pure copper powder is 10:1, wherein the particle size of the pure copper powder is -100 mesh; The copper-tin-11 alloy powder is mixed with 10%, 12% or 13% of the pure copper powder, 0.1% of phosphor copper powder and 0.5% of lubricant.
2. The method for preparing high performance copper-tin-10 alloy powder according to claim 1, characterized in that: In the primary mixing, the composition ratio of the copper-tin-13 alloy powder to the pure copper powder is 10:3, wherein the bulk ratio of the copper-tin-13 alloy powder is 3.15-3.33 g / cm 3 The particle size is between -325 mesh ≥75%; the looseness ratio of the pure copper powder is ≤2.6g / cm 3 , Particle size -325 mesh ≥75%.
3. The method for preparing high performance copper-tin-10 alloy powder according to claim 1, characterized in that: In the diffusion reduction, the reduction temperature of the copper-tin primary mixed powder is 540-600° C., and the reduction time is 160 min-180 min.
4. The method for preparing high performance copper-tin-10 alloy powder according to claim 1, characterized in that: In the crushing and screening, a fine crusher and a screening machine are used to crush and screen the copper-tin-11 aggregates. The frequency of the fine crusher is set to 20 Hz, and the crushing mesh is -80 mesh. The bulk ratio of the copper-tin-11 alloy powder after screening is 2.45-2.55 g / cm 3 Between, particle size -325 mesh ≤40%.
5. The method for preparing high performance copper-tin-10 alloy powder according to claim 1, characterized in that: The smelting and mixing adopts high-temperature smelting, and the smelting temperature is 1100° C. to 1200° C., and the electrolytic copper and the tin ingot are smelted to form an alloy liquid phase.
Citation Information
Patent Citations
Preparing method of copper-tin 10 alloy powder for powder metallurgy
CN105458275A